Canagliflozin ameliorates high-salt-induced renal injury and premature aging in male Dahl salt-sensitive rats, with associated changes in SIRT6/HIF-1α signaling - Qiuyan Wang; Yi Liang; Qingjuan Zuo; Lili He; Tingting Zhang; Zhongli Wang; Jianlong Zhai; Boce Cao; Sai Ma; Guorui Zhang; Fan Lu; Yifang Guo (Renal Failure)
Sodium–glucose cotransporter 2 inhibitors (SGLT2is) exhibit renoprotective effects in diabetic and nondiabetic patients; however, the underlying mechanism remains unclear. This study aimed to investigate the effects of canagliflozin (an SGLT2i) on salt-sensitive hypertensive kidneys. Male Dahl salt-sensitive rats were fed a high-salt (8%) diet and then orally administered canagliflozin 30 mg/kg/day or 0.5% hydroxypropyl methylcellulose solution for 12 weeks. Thus, a high-salt-induced model of hypertensive kidney injury with premature aging was established to evaluate the protective effects and related mechanisms of canagliflozin on hypertensive kidneys. Canagliflozin reduced blood pressure, the serum creatinine concentration, and urinary albumin excretion in high-salt rats. Hematoxylin and eosin, Masson, and senescence-associated β-galactosidase (staining were performed on rat kidneys, revealing that canagliflozin alleviated renal fibrosis and premature aging. Immunohistochemical analysis and protein detection demonstrated that canagliflozin increased the expression of silent information regulator 6 (SIRT6) in the kidney, inhibited the expression of the hypoxia-inducible factor-1 alpha (HIF-1α) protein and its target genes, and alleviated kidney damage and premature aging. In summary, canagliflozin ameliorates renal injury and premature aging in male Dahl salt-sensitive rats fed high salt with associated changes in SIRT6/HIF-1α signaling.